The political economy of state regulation: The case of the English Factory Acts - Katherine A. Moos (University of Massachusetts, Department of Economics, 2017)
This paper proposes a theory of why the state enacted social policy that regulated the length of the working day in 19th century industrial England. This paper will argue that, far from being capable of self-regulation, the capitalist labor market during Britain's industrial revolution is best conceptualized as consisting of two major social coordination problems resulting from conflicting interests between and within capital and labor. Left unregulated, this dual social coordination problem caused the overexploitation of labor, with dire consequences for both the capitalist and working classes. The reason why this coordination problem could not self-correct was because the wage-labor bargain contained the externality of unwaged household labor. The existence of this externality became deleterious to firms' profitability and workers' survival, especially given the high levels of female labor force participation. This social coordination problem justified and required state regulation into industrial relations. By conceptualizing protective policy as the solution to a dual social coordination problem caused by conflicting interests among heterogeneous firms and workers, this paper extends the Polanyian framework with an explicit theory of exploitation based on the classical theory of competition and a feminist emphasis on social reproduction and unwaged labor.
Keywords: B54; C72; J88; N3; 330; English Factory Legislation; Social Coordination Problem; Game Theory; Labor Policy; Regulation; Hours of Work; Child Labor; Female Labor Force Participation